Implementation of Performance Management to Optimize the Role of English Teachers in the Learning Process at Pusdikpengmilum - Aspani, Rony; Ferry Cahaya, Yohanes (Dinasti Publisher, 2025)
This study aims to analyze the implementation of performance management to optimize the role of English teachers in the learning process at the Pusdikpengmilum military education institution. The research method used is qualitative with a case study approach. Data were collected through in-depth interviews, participatory observations, and document analysis. The research sample includes English teachers and management at Pusdikpengmilum. The results show that structured performance management implementation through planning, execution, and evaluation enhances teacher competencies. Continuous training, data-driven performance evaluations, and comprehensive managerial support prove effective in fostering innovative and relevant teaching methods. The study recommends strengthening integrated policies to improve education quality in military institutions.